Estimating precipitation phase using a psychrometric energy balance method. Issue 13 (20th May 2013) - Harder, Phillip; Pomeroy, John; Carey, Sean; Buttle, Jim
Abstract Precipitation phase is fundamental to a catchment's hydrological response to precipitation events. Phase is particularly variable over time and space in the Canadian Rockies where snowfall or rainfall can occur any month of the year. Phase is controlled by the microphysics of the falling hydrometeor, but microphysical calculations require detailed atmospheric information that is often lacking for hydrological analyses. In hydrology, there have been many methods developed to estimate phase, but most are regionally calibrated, and many depend on air temperature (Ta) and use daily time steps. Phase is not only related to Ta, but to other meteorological variables, and precipitation events are temporally dynamic, adding uncertainty to the use of daily indices to estimate phase. To better predict precipitation phase, the psychrometric energy balance of a falling hydrometeor was calculated and used to develop a method to estimate precipitation phase. High quality precipitation phase and meteorological data were observed at multiple elevations in a small Canadian Rockies catchment, Marmot Creek Research Basin, at 15‐min intervals over several years to develop and test the method. The results of the psychrometric energy balance method were compared to phase observations, to other methods over varying time scales and seasons and at varying elevations and topographic exposures. The results indicate that the psychrometric energy balance method performs much better than Ta index methods and that this improvement, and the accuracy of the psychrometric energy balance method, increases as the time step of calculation decreases. Copyright © 2013 John Wiley & Sons, Ltd.